Improvement of engineering properties of liquefied soil using Bio-VegeGrout - Baharuddin I.N.Z.; Omar R.C.; Devarajan Y. (Institute of Physics Publishing, 2023)
Lab tests were carried out in order to analyze and investigate the liquefaction behavior of marine deposit soil which was placed in the region of LCCT, Sepang. The soil was found exposed to liquefaction. Step to improvise the soil was to inject Biovege grout into the soil sample. Soil sample was prepared with three different grout amount, 10%, 25% and 50%. The relation between percentage of Biovege grout injected and soil improvement were observed and recorded. The void ratio and the permeability of the soil sample decreased with increasing grout percentage. The soil becomes stiffer as the amount of grout used increase. The results obtained indicate, higher amount of grout injection reflects better soil improvement in term of cohesion, friction angle, shear stress and void ratio. The Biovege grout increases the resistance of soil against liquefaction Published under licence by IOP Publishing Ltd.